Ethics and aesthetics in European modernist literature : from the sublime to the uncanny - Ellison, David R. (Cambridge University Press, 2001)
Ellison's book is an ambitious presentation of the aesthetic and ethical dimensions of Modernist literature. Ellison brings together philosophical, theoretical, and literary texts ranging over a century and a half of intellectual history. He shows, through close readings, how the struggle between aesthetic and ethical issues characterises each of them.